The Impact of Artists on Contemporary Urban Development in Europe - Murzyn-Kupisz, Monika; Działek, Jarosław (Springer International Publishing : Imprint: Springer, 2017)
This book provides an up-to-date, critical review of theoretical concepts connecting artists and urban development. It focuses on the multidimensionality of potential and actually observed interactions between artists and cities and their impacts on urban space, its form, functions and perceptions. Departing from the viewpoint that a more nuanced geography of artists is still needed to fully conceptualise the diversity of roles artistic creatives play in urban transformations, the book presents contributions with a common denominator of distinguishing artists as a unique professional and social group. The essays focus on the complexity of the artists' spatial preferences and analyse a myriad of expressions of artists' presence in urban centres in different geographic, political, economic, social, and spatial contexts drawing on experiences from 16 cities across Europe. The book presents several case studies ranging from Spain to Russia and from Scandinavia to Slovenia, and offers new pathways into understanding the implications of artists' residence and activities in contemporary cities. Apart from presenting less obvious expressions of artists' involvement in urban transformations such as their participation in urban planning or grass root urban movements, the volume explores the ambivalence of artists' interactions with cities. Particular chapters test several divergent narratives of artistic creatives as inspirers and instigators of urban changes, pioneers of gentrification, contesters and resisters of neoliberal urban policies or mere indicators of transformations inspired by other actors, instrumentalized by public and private stakeholders. .
Keywords: Social sciences.; Culture -- Study and teaching.; Arts.; Economic geography.; Urban geography.; Human geography.; elektronické knihy; electronic books